#### Answer

x=-2

#### Work Step by Step

Simplifying
5x + -7 = 6x + -5
Reorder the terms:
-7 + 5x = 6x + -5
Reorder the terms:
-7 + 5x = -5 + 6x
Solving
-7 + 5x = -5 + 6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-6x' to each side of the equation.
-7 + 5x + -6x = -5 + 6x + -6x
Combine like terms: 5x + -6x = -1x
-7 + -1x = -5 + 6x + -6x
Combine like terms: 6x + -6x = 0
-7 + -1x = -5 + 0
-7 + -1x = -5
Add '7' to each side of the equation.
-7 + 7 + -1x = -5 + 7
Combine like terms: -7 + 7 = 0
0 + -1x = -5 + 7
-1x = -5 + 7
Combine like terms: -5 + 7 = 2
-1x = 2
Divide each side by '-1'.
x = -2
Simplifying
x = -2